Types of Feed Preferred by Double Jowls Cassowary (Casuarius casuarius Linn 1758) in Taman Safari Gurun Putih Lestari, Aceh Besar - Nur Aiza Amalia; Abdullah Abdullah; Devi Syafrianti; Khairil Khairil; Asiah MD (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
The IUCN Redlist has included the double jowls cassowary in the vulnerable conservation status since 1994, so it is necessary to do ex situ conservation. Taman Safari Gurun Putih Lestari is one of the ex situ conservation areas in Aceh. The success of captive activities is influenced by several aspects, one of which is the provision of the type of feed. Feeding is very important in fulfilling animal nutrition for growth. The purpose of the research was to determine the level of feed palatability and the type of feed preferred by double jowls cassowary in Taman Safari Gurun Putih Lestari, Aceh Besar. The approaches used in this research are quantitative and qualitative approach. The method used is direct observation. The results of this study were the double jowls cassowary in cage I consumed 96.75% of banana, 93.32% of papaya, and 72.07% of cucumber. While the double jowls cassowary in cage II consumed 97.46% of banana, 92.89% of papaya, and 63.53% of cucumber.. The level of sweetness of the three types of feed has a different level of sweetness, namely banana very sweet with a sucrose amount of 12.1°Brix, papaya sweet with an 8.3°Brix amount of sucrose, and slightly sweet cucumber with a sucrose amount of 2.9°Brix. The conclusion of this research are the level of feed palatability of the double jowls cassowary belongs to the category of high palatability class and the most preferred type of feed is banana because of its sweet taste and soft texture.Keywords: feed, palatability, double jowls cassowaryIUCN Redlist memasukkan burung kasuari gelambir ganda dalam status konservasi rentan (vulnerable) sejak tahun 1994, sehingga perlu dilakukan konservasi secara ex situ. Taman Safari Gurun Putih Lestari merupakan salah satu konservasi ex situ di Aceh. Keberhasilan kegiatan penangkaran dipengaruhi oleh beberapa aspek salah satunya adalah pemberian jenis pakan. Pemberian pakan sangat penting dilakukan untuk pemenuhan gizi satwa bagi pertumbuhan. Tujuan dilakukan penelitian yaitu untuk mengetahui tingkat palatabilitas pakan dan jenis pakan yang disukai burung kasuari gelambir ganda di Taman Safari Gurun Putih Lestari, Aceh Besar. Pendekatan yang digunakan pada penelitian ini berupa pendekatan kuantitatif dan kualitatif. Metode yang digunakan adalah direct observation. Hasil dari penelitian ini adalah pisang bertekstur lunak, pepaya bertekstur lunak-berair, dan mentimun bertekstur keras-berair serta ketiga jenis pakan memiliki tipe buah sejati tunggal atau buah buni. Tingkat kemanisan daripada ketiga jenis pakan memiliki tingkat kemanisan yang berbeda yaitu pisang sangat manis dengan jumlah sukrosa 12,1, pepaya rasanya manis dengan jumlah sukrosa 8,3, dan mentimun agak manis dengan jumlah sukrosa 2,9. Simpulan dari penelitian ini adalah jenis pakan yang paling disukai yaitu pisang karena rasanya yang manis dan bertekstur lunak.Kata kunci: pakan, palatabilitas, burung kasuari gelambir ganda